Role of perfusion index in pulse oximetry screening for critical congenital heart disease in neonates - Ramesh, S; Kumutha, J (Indian Journal of Child Health, 2018)
Introduction: Screening for critical congenital heart diseases (CCHD) with oxygen saturation (SpO2) by pulse oximeter often misses left-sided obstructive heart diseases. Objective: The role of perfusion index (PI) along with SpO2 in CCHD screening was studied. Methodology: The Masimo, RADICAL-7 pulse oximeter was used to record the SpO2 and PI in the right hand and left foot of asymptomatic babies at 24–72 h of life. Babies with SpO2